Prehistoric hilltop settlement Gradišče on Primskovo in the Dolenjska region - Pavlin, Primož (Arheološki vestnik, 2022)
During the excavations carried out in 1998, we determined that Gradišče was inhabited in five different archaeological periods. The earliest visits to the hill date back to the Neo-Eneolithic, when it was not yet fortified. In the Late Bronze Age, the settlement had received a wooden formwork filled with earth, which ended in a fire. In both parts of the Iron Age, the settlement was surrounded by a wall of dry-stone masonry. In the Hallstatt period, the wall was about 2 metres wide; in the La Tène period, it was narrower and measured about 1.2 metres in width. Stray finds testify to the presence of man as early as Late Antiquity. However, as there are no traces of fortifications from this period, the hill probably served as an occasional refuge.